2001
DOI: 10.1056/nejm200105173442001
|View full text |Cite
|
Sign up to set email alerts
|

Serratia liquefaciensBloodstream Infections from Contamination of Epoetin Alfa at a Hemodialysis Center

Abstract: Puncturing single-use vials multiple times and pooling preservative-free epoetin alfa caused this outbreak of bloodstream infections in a hemodialysis unit. To prevent similar outbreaks, medical personnel should follow the manufacturer's guidelines for the use of preservative-free medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(67 citation statements)
references
References 7 publications
0
65
0
2
Order By: Relevance
“…All of the S. liquefaciens isolates were identical by PFGE, and the outbreak stopped when pooling of epoetin alfa was discontinued and the soap and lotion were replaced. All of the patients recovered with antimicrobial therapy (171).…”
Section: S Liquefaciensmentioning
confidence: 94%
See 1 more Smart Citation
“…All of the S. liquefaciens isolates were identical by PFGE, and the outbreak stopped when pooling of epoetin alfa was discontinued and the soap and lotion were replaced. All of the patients recovered with antimicrobial therapy (171).…”
Section: S Liquefaciensmentioning
confidence: 94%
“…Like S. marcescens, S. liquefaciens is an environmental organism that has been associated with infections from contaminated medical devices, products, and equipment, including a vitamin C infusion (123), pressure-monitoring equipment (175), neonatal enteral feeding tubes (193), Alsever's solution (252), and endoscopes (261). There have also been several described instances of contaminated blood products with associated transfusion reactions in humans (44,117,171,200,326,412).…”
Section: S Liquefaciensmentioning
confidence: 99%
“…Although the overall risk for extrinsic contamination of multidose vials is likely minimal [168], the consequences of contamination might result in lifethreatening infection [169,170]. Single-use vials are frequently preservative-free and might pose a risk for contamination if they are punctured several times.…”
Section: Multidose Parenteral Medication Vialsmentioning
confidence: 99%
“…During an outbreak investigation of S. liquefaciens, BSI, and pyrogenic reactions in a haemodialysis centre, pathogens were isolated from extrinsically contaminated vials of medication resulting from multiple dose usage, antibacterial soap, and hand lotion. 161 Duckro and colleagues 126 showed that VRE could be transferred from a contaminated environment or patients' intact skin to clean sites via the hands of HCWs in 10.6% of contacts.…”
Section: Cross-transmission Of Organisms By Contaminated Handsmentioning
confidence: 99%